IMPLEMENTASI AKUNTANSI MANAJEMEN SEKTOR PUBLIK TERHADAP PENETAPAN TARGET PENDAPATAN DI CABANG PELAYANAN BADAN PENDAPATAN DAERAH PROPINSI JAWA BARAT - Rukmi Juwita; Riani Tanjung; Rima Sundari (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2018)
Abstract: This research aims to study management accounting implementation in managers' decisions for setting targeting goals in service revenue of West Java province. Public sector management accounting is defined as relevant and reliable accounting information aimed at leaders with a view to planning (strategic planning, information delivery, investment assessment, budgeting, service costing, performance appraisal) and control (measuring management performance achievement by means of the achievement of targets that are in accordance with the planned program. The Vehicle Tax is the potential of substantial local taxes for revenue revenues in the western Java province. The results showed that Management Accounting has a strong relationship with Target Income Determination at West Java Provincial Income Board. Meanwhile, if seen from the result of regression equation, regression coefficient from independent variable marked positive which indicate that the implementation of good Management Accounting will increase Target Income of Regional Income Board in West Java province.Keywords: Public Sector Management Accounting, Regional Income, Motor Vehicle Tax.